Aṡaru Al-Siyāq Al-Qurānī Fī Tafsīr Al-Qurān Al-karīm I‘nda Ibnu A‘syūr fī Tafsīr Al-Taḥrīr wa Al-Tanwīr Surah (Qāf) Anmūżajan: أثر السياق القرآني في تفسير القرآن الكريم عند ابن عاشور في تفسير التحرير والتنوير سورة (ق) أنموذجا - Oryzafani, Muhammad Iqbal; Saket, Saeed Abdullah Saeed; Rabbani, Muhammad Aqil; Erlina, Lira (PT. Student Rihlah Indonesia, 2022)
This research aims to explain the types of contexts in the Qur'an and to elucidate their significant impact on the interpretation of the Qur'an. The research follows a descriptive analytical approach by examining the words of Imam Sheikh Muhammad Al-Tahir Ibn Ashur in his interpretation, as well as relevant reference materials and books of tafsir associated with his work. The approach involves classifying, collecting, analyzing, and presenting the data while understanding the rules and foundations of his interpretation.This research demonstrates that Imam Muhammad Al-Tahir Ibn Ashur placed great emphasis on the context of the Qur'an. It also proves that there is no repetition within the Qur'an and that understanding its context is highly beneficial for interpreting its texts.